Instagram: Alternatif Media dalam Pengembangan Maharah Al-Kitabah - Noor Amalina Audina; Muassomah Muassomah (Universitas Islam Negeri Palangka Raya, 2020)
This study aims to show that Instagram, which has only been popular for posting photos or videos, is very effective as a medium of al-Kitabah learning and can increase the ability of the students in al-Kitabah Maharah. In addition, it shows positive and negative responses of students to the use of Instagram as al kitabah maharah learning media. The study uses a qualitative descriptive approach and data and information were collected by using observation, interviews and documentation. Data analysis techniques used Miles and Huberman models, namely data reduction, data presentation and data verification. The results of this study indicate that Instagram is one of the social media that strongly supports and motivates students to create and innovate in writing without being limited to place and time. Based on the results of the questionnaire, it was obtained a very positive response from 21 students that all students agreed with the use of Instagram as a medium for learning al-Kitabah maharah. Students give positive responses because they are flexible, not limited in time, learning is more varied and students are more active and creative. As for the negative responses of students needing an internet connection, teachers do not control directly. Researchers hope that with this study, the teachers can use the Instagram application as a medium for learning Arabic, so students can wisely utilize social media.